Effects of enzymatic cross-linking combined with ultrasound on the oil adsorption capacity of chickpea protein. (30th July 2022) - Zhu, Guobin; Li, Yueqin; Xie, Li; Sun, Huizi; Zheng, Zhi; Liu, Fengru
Graphical abstract: Highlights: Treatment of chickpea protein by enzyme crosslinking combined with ultrasound. The oil adsorption capacity of modified chickpea protein was improved ( p < 0.05). This method can further improve the stability of emulsification and emulsification. This method can reduce the particle size of the chickpea protein after crosslinking. This method currently has great potential for chickpea protein modification. Abstract: In order to improve the oil adsorption capacity of chickpea protein, enzymatic cross-linking combined ultrasound was used to modify chickpea protein. Electrophoretic results showed that enzymatic cross-linking made the protein bands thinner, but ultrasound had no significant effect. The oil adsorption capacity of chickpea protein increased from 1.88 to 2.43 g/g; the surface hydrophobicity increased from 3933 to 4575; the zeta potential and emulsification performance were improved. After enzymatic cross-linking, the content of the free sulfhydryl group and emulsifying stability were decreased, and the particle size and the content of disulfide bonds were increased. After ultrasonic treatment, these properties showed an opposite trend. Fourier Transform Infrared Spectroscopy showed that β-turn and random coil increased, the structure of protein became more loose and disordered. These results indicate that enzymatic cross-linking combined with ultrasound improves the functional properties of chickpea protein and extends its application.